The Evolution of the Conceptual Scope of Marketing and Changes in the Areas, Methods and Techniques of Research - Mazurek-Łopacińska, Krystyna; Sobocińska, Magdalena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
This paper examines the ongoing changes in marketing research brought about by the development of marketing discourse. Given the interdisciplinary character of marketing, which has made such research develop as a multi-paradigmatic science, it is important to show the applications of social studies paradigms to marketing and marketing research, including the neopositive-functional-systematic, the interpretative-symbolic, the radical structuralist and the postmodernist paradigms. How marketing research is developing is also shown in the context of expectations rising as a result of ever greater changes in the market and the use of new technologies in marketing research, which broaden the possibilities for gathering information for business management.